Formulation, Development and Evaluation of a Polyherbal Tablet Containing Moringa oleifera and Carica papaya Leaf Extracts for the Management of Thrombocytopenia - Chandel, Bhoomika; Sahu, Gyanesh Kumar; Sharma, Harish; Chaudhary, Maheshwari; Deshmukh, Jineshwari; Vishwakarma, Pallavi; Shukla, Aditi; Netam, Purnima; Sahu, Balram; Malakar, Chitrendra (International Journal of Aquatic Research and Environmental Studies, 2026)
A low platelet count, or thrombocytopenia, increases the risk of bleeding and delayed clotting. Because of their high concentration of flavonoids, alkaloids, and phenolic chemicals, herbal remedies—in particular, Moringa oleifera and Carica papaya leaves—have historically been shown to improve platelet synthesis. The purpose of this study were to create and assess a herbal pill that might be used to treat thrombocytopenia. Fresh leaves were gathered, verified, cleaned, dried in the shade, and ground into a powder. The direct compression method were used to make tablets with conventional excipients after the powdered material were extracted using appropriate solvents. The physical characteristics of the prepared tablets, such as weight homogeneity, hardness, friability, disintegration time, and in vitro dissolution, were assessed, along with the phytochemical content. The tablets met pharmacopeial criteria and preserved significant bioactive ingredients, according to the results, suggesting that they may be effective in promoting platelet synthesis. This study shows that creating a standardized herbal pill from Moringa oleifera and Carica papaya leaves is feasible as a supplemental strategy for managing thrombocytopenia.